PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN APLIKASI CANVA UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI BILANGAN BERPANGKAT - Siti Aisyah Hasibuan; Mariam Nasution; Anita Adinda (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2026)
This project aims to develop a differentiated learning-based instructional medium using the Canva application to improve students' conceptual understanding and problem-solving skills in the domain of exponents. This study employed the five stages of the ADDIE development model: analysis, design, development, implementation, and assessment. The subjects were eighteen eight-graders from SMP Negeri 1 Batahan. Among the instruments used were expert validation sheets, teacher and student response questionnaires, and tests for conceptual understanding and problem-solving abilities. The results showed that, in terms of conceptual understanding and problem-solving, the produced media had exceptionally high levels of validity (average percentage of 92.02%), practicality (92.00%), and efficacy in the "fairly effective" (N-Gain of 53%) and "moderate" (N-Gain of 51%) categories, respectively. The Paired Sample T-Test revealed significant differences between pretest and posttest scores for both conceptual comprehension (t_calculated = 6.94 t_table = 2.571) and problem-solving (t_calculated = 6.29 t_table = 3.182). As a result, it has been demonstrated that personalized learning resources created using Canva are dependable, practical, and effective in improving students' learning results in exponentiation-related subjects.